2000
DOI: 10.2527/2000.7882108x
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimates for greasy fleece weight of Rambouillet sheep at different ages.

Abstract: Variance components for greasy fleece weight in Rambouillet sheep were estimated. Greasy fleece weight was modeled either as repeated measurements on the same trait or as different traits at different ages. The original data were separated according to the age of the ewe at shearing into three classes; 1 yr, 2 and 3 yr, and older than 3 yr. An animal model was used to obtain estimates of genetic parameters with a REML algorithm. Total numbers of animals in pedigrees for the different age classes were 696, 729,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
2
5
0
1
Order By: Relevance
“…The lower estimates for reproductive traits indicate the presence of lower additive genetic variance as they are largely influenced by environment factors. Lee et al (2000) and Khan et al (2015) reported similar estimates for GFW. Moderate to high heritability estimates for production traits suggested presence of sufficient additive genetic variance which could be utilized for improvement.…”
Section: Genetic Parametersmentioning
confidence: 54%
“…The lower estimates for reproductive traits indicate the presence of lower additive genetic variance as they are largely influenced by environment factors. Lee et al (2000) and Khan et al (2015) reported similar estimates for GFW. Moderate to high heritability estimates for production traits suggested presence of sufficient additive genetic variance which could be utilized for improvement.…”
Section: Genetic Parametersmentioning
confidence: 54%
“…However, lower estimates of heritability for greasy fleece weight at 12 months of age were reported by Fogarty (1995) in meat breeds (0.19) and Nagy et al. (1999) in a Hungarian dual‐purpose breed (0.12), and higher estimates have been reported for several dual‐purpose breeds (Notter & Hough 1997; Lee et al. 2000; Hanford et al.…”
Section: Resultsmentioning
confidence: 83%
“…The power to detect association for hip OA in our report was a limiting factor as only 99 dogs were available for this analysis and only the Labrador retrievers and the crosses to Greyhounds were included for this phenotype. Within dog breeds on average, LD is extensive (0.5–1.0 Mb), whereas across breeds, the extent of LD is less than 10 Kb [18], [19], [52]. Labrador retrievers are diversified even within breed as illustrated in Figure S5 .…”
Section: Discussionmentioning
confidence: 99%